Digital health education as a topic for PE: Relevance, practical implications, and teachers' perspectives - Andreas Raab (Bern Open Publishing, 2023)
Digital health technologies and social networking services have become an inherent part of physical activity, exercise routines and fitness training. Adolescents obtain significant parts of their health-related knowledge and beliefs from such technologies and social media, which in turn can influence how they approach sports and physical activity. These processes have been accelerated and intensified by the Covid-19 pandemic. Against this background, this paper aims to discuss the relevance of digital health education as a topic for the subject PE. First, potential benefits and risks of digital health technologies and networks are explained with a focus on adolescents as the target group for digital health education. In this context ideas and recommendations to implement digital health education in teaching practices are illustrated. It is argued that young people should be supported to develop their own critical viewpoints and attitudes towards the use of digital health technologies and networks to pursue individual health-related goals. Second, results from a qualitative interview study with 32 PE teachers in Austria regarding their perspectives on digital health education in PE are presented. The most significant findings of the survey are that asked teachers see digital technology mainly as a tool for functional health promotion and are aware of normative body representations in social networks. Some PE teachers also orchestrate PE as a counterpart to an increasingly digitalized world excluding digital technology form their lessons. However, a holistic approach to digital health education requires that the digital culture of health, body, exercise and fitness is experienced and discussed from different perspectives. In doing so, students can be enabled to use digital health technologies and networks in an informed, responsible and self-determined way.